Naxalism in India: present and future challenges - Kumar, Sanjay (ed.); Hussain, M. Samir (ed.) (New Delhi G.B. books, 2015)
The present volume has comprehensive addressed the several issues related to naxal problem and the counter strategy to tackle it.
Keywords: Naxalism